The effect of cultivation technologies on chickpea productivity in the southern part of the Rostov region - S. A. Vasilchenko; G. V. Metlina (Зерновое хозяйство России)
The field trials were carried out in 2018–2019 in the laboratory for cultivation technology of row crops of the FSBSI “AgriculturalResearchCenter“Donskoy” (Zernograd). The experimental plot is located in the southern agricultural part of theRostovregion characterized with insufficient and unstable moisture. The soil of the experimental plot is ordinary heavy loamy blackearth (chernozem) on loess-like loam, with 3.2% of humus, 18.5–20.0 of P O , 342–360 mg of K O per a kg of soil. The value of the hydrothermal coefficient in the years of study ranged from 0.28 to 0.55 (insufficient moisture supply of the growing season). The current paper has presented the study results of the effect of effect of seeding rates, sowing dates, sowing methods on productivity of the middle early ripening chickpeas variety “Privo1”. The applied agricultural techniques affected on indicators of the yield structure elements. So, the increase of the seeding rate from 0.3 to 1.0 million units/ha reduced number of seeds per plant by 7–11 pcs., decreased seed weight per plant by 1.7–2.6 g and 1000-seed weight by 35–65 g. The sowing date had the greatest effect on chickpea productivity (the effect of the factor was 42.2%), and the sowing method had the smallest (4.1%) effect on it. The largest productivity was formed in the first period with the ordinary-row method of sowing (0.76–1.06 t/ha), and the smallest productivity was formed in the third period with the wide-row method of sowing (0.44–0.71 t/ha). The correlation between the main elements of productivity (“number of seeds per plant”, “seed weight per plant”, “1000-seed weight”) and cultivation technologies was average positive (r = 0.39–0.47).